Synthesis and Characterization of Hydroxyapatite/chitosan Composite Material for Medical Enginering Applications - Vuong, Bui Xuan (VNU Journal of Science: Natural Sciences and Technology, 2018)
This study is to synthesize the HA-Chitosan composite materials for medical enginerging applications. XRD and SEM analyses confirmed the precipitation and dispersion of HA on the structural network of chitosan polymer material. The dispersion of HA particles depended on the concentration of the chitosan solution. The volumetric mass density and Compressive strength of composite HA-Chtosan were also determined. These values increased as a function of modeling press. In addition, volumetric mass density and compressive strength in composite containing higher chitosan had higher values. Keywords Hydroxyapatite (HA), chitosan, characterization, modeling press, compressive strength References [1] Hench LL. Bioceramics. J Am Ceram Soc 1998;81:1705–28. [2] D. F. Williams, Definitions in Biomaterials, Consensus Conference for the European Society for Biomaterials, Chester, UK, 1986. [3] L. Sopyan, R. Singh and M. Hamdi, ‘‘Synthesis of nano sized hydroxyapatite powder using sol - gel technique and its conversion to dense and porous bodies,’’ Indian Journal of Chemistry, vol.47A, pp. 1626-1631, Nov.2008. [4] A.K. Nayak, ‘‘Hydroxyapatite Synthesis Methodologies: An Overview,’’ International Journal of ChemTech Research, vol.2, pp. 903-907, Apr.2010. [5] Griffon DJ, Sedighi MR, Schaeffer DV, Eurell J, Johnson AL. Chitosan scaffolds: interconnectivity pore size and cartilage engineering. Acta Biomater 2006;2:313–20. [6] Wang X, Ma J, Wang Y, He B. Bone repairs in radii and tibias of rabbits with phosphorylated chitosan reinforced calcium phosphate cements. Biomaterials 2002;23:4167–76. [7] Johnson JW, Herschler A. A review of the mechanical behavior of CaP and CaP/ polymer composites for applications in bone replacement and repair. Acta Biomater 2011;7:16–30. [8] Oliveira JM, Rodrigues MT, Silva SS, Malafaya PB, Gomes ME, Viegas CA, et al. Novel hydroxyapatite/chitosan bilayered scaffold for osteochondral tissueengineering applications: Scaffold design and its performance when seeded with goat bone marrow stromal cells. Biomaterials 2006;27:6123–37. [9] Khanna R, Katti KS, Katti DR. In situ swelling behavior of chitosanApolygalacturonic acid/hydroxyapatite nanocomposites in cell culture media. Int J Polym Sci 2010;10:12. [10] Albano C, Perera R, Catano L, Karam A, Gonzalez G. Prediction of mechanical properties of composites of HDPE/HA/EAA. J Mech Behav Biomed Mat 2011;4:467–75. [11] XRD pattern of HA: JCPDS PDF no. 09-432.